Digestive symptoms and liver injury in patients with coronavirus disease 2019 (COVID‐19): A systematic review with meta‐analysis. Issue 6 (28th October 2020) - Wan, Jian; Wang, Xuan; Su, Song; Zhang, Yujie; Jin, Yirong; Shi, Yanting; Wu, Kaichun; Liang, Jie
Abstract: Although most COVID‐19 patients typically present with respiratory symptoms, many patients could experience digestive symptoms as the major complaint. We performed a systematic review and meta‐analysis to investigate the exact prevalence of digestive symptoms and liver injury in COVID‐19 patients and compare the difference between patients with and without digestive symptoms. PubMed, Embase, Ovid, Wanfang data, and CNKI were searched until 24 April 2020 to identify studies that reported digestive symptoms and liver injury in COVID‐19 patients. A random‐effect model was used to combine the data. Finally, 64 studies with 15 141 patients were included. The pooled rate of digestive symptoms and liver dysfunction was 31.8% (95 CI 21.0–42.5%, I 2 = 97.6%) and 27.4% (95 CI 16.9–37.9%, I 2 = 97.9%), respectively. Patients with digestive symptoms were more likely to present with fatigue (OR 2.28, 95 CI 1.66–3.14, P < 0.00001, I 2 = 31%), myalgia (OR 1.96, 95 CI 1.06–3.65, P = 0.03, I 2 = 69%), and acute respiratory disease syndrome (ARDS) (OR 2.94, 95 CI 1.17–7.40, P = 0.02, I 2 = 0) and had a trend to present as severe/critical type (OR 1.87, 95 CI 0.98–3.57, P = 0.06, I 2 = 58%). Severe/critical patients were more likely to present with diarrhea (OR 2.02, 95 CI 1.16–3.50, P = 0.01, I 2 = 64) and have high alanine aminotransferase (ALT) (OR 2.08, 95 CI 1.55–2.81, P < 0.00001, I 2 = 13%, ) and aspartate aminotransferase (AST) (OR 3.53, 95 CI 2.76–4.51, P < 0.00001, I 2 = 0). The pooled rate of patients with digestive symptoms was 28.7% (95 CI 17.6–39.8%) and 42.8% (95 CI 23.4–62.3%) in studies from China and out of China, respectively. COVID‐19 patients had a high rate of digestive symptoms and liver injury. Patients with digestive symptoms had a trend to develop severe/critical illness. Abstract : COVID‐19 patients had a high rate of digestive symptoms and liver injury. Patients with digestive symptoms had a trend to develop severe/critical illness.